FLANDERS INTERACTION ANALYSIS (FIA) IN ANALYZING TEACHER-STUDENT INTERACTION IN EFL CLASSROOM BASED ON 2013 CURRICULUM - Retna Fauziah Adhitya Rini (Journal of English Education Program (JEEP), 2014)
This study investigated teacher-students interaction in EFL classroom that implements 2013 curriculum. This study focused on the kind as well as the characteristic of teacher-students interaction in EFL classroom that implements 2013 curriculum. In analyzing the data, this study was analyzed by means of Flanders Interaction Analysis. Flanders Interaction Analysis is a system that aims to measure the classroom interaction which has 10 categories, namely accepting feeling, praising and encouraging, accepting or using ideas of student, asking questions, lecturing, giving directions, criticizing or justifying authority, student-talk response, student-talk initiation and silence (Walsh, 2011). In this regard, two questions are addressed : 1) What kinds of teacher-students interaction occurred in EFL classroom that implements 2013 curriculum based on Flanders Interaction Analysis? and 2) What is characteristic of teacher-students interaction reflected in EFL classroom that implements 2013 curriculum based on Flanders Interaction Analysis?. To obtain the data, classroom observations were conducted in two English classes of Peminatan (Optional) program at the tenth grade in one of Senior High School in Ciamis which implements 2013 curriculum. Then, two English teachers and sixty students were selected purposively. The findings revealed that the kinds of teacher-students interaction occurred in both classes were dominated by teacher talk through emphasizing on asking question. In the case of teacher A, from the total of teacher talk (72.29%), teacher A used asking question (27.56%). While in the case of teacher B, from the total of teacher talk (64.93%), teacher B used asking question (25.97%). In terms of characteristic of teacher-students interaction, the characteristic in both classes was content-cross. In the case of teacher A, the percentage of content-cross was 43.83%, while the percentage of content-cross of teacher B was 38.34%. From the findings above, it could be inferred both teachers used asking questions and lecturing to interact with the students. In line with the implementation of 2013 curriculum, both teachers have not been comprehended the implementation of 2013 curriculum due to the dominance of teacher talk in teacher-student interaction during teaching and learning process.